Analisis faktor – faktor yang mempengaruhi kepuasan pengguna aplikasi mobile IPOT - Taufik Abdul Azeis; Kisti Nur Aliyah (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2023)
This research aims to determine the effect of completeness of features, ease of use, and low transaction costs on the satisfaction of using the IPOT mobile application. This research uses a quantitative research method with data analysis techniques, namely multiple linear regression. The data source for this study uses primary data sources which are assisted in processing by IBM SPSS 23 software The results of this research indicate that simultaneously and partially, the variables of feature completeness, ease of use, and low transaction costs have a positive and significant influence on the satisfaction of using the IPOT mobile application This research can provide a basis for other researchers conducting other similar studies to increase the satisfaction of users of the Mobile IPOT application